Orlando and its Genre Ambiguity (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Orlando is a novel which is difficult to define regarding the literary genre. It is sometimes considered a phantasy – biography, philosophical biography, novel about writers, parody of a biography and the author herself named it as a „writer's holiday“. The aim of the paper is to point out to new possibilities of interpreting Orlando as a parody of a Bildungsroman. The Bildungsroman is considered as a bond between an autobiography (Jacobs and Krause, Dilthay) and picaresque novel (Miles). The paper challenges the real historical time in the novel and the role of the omniscient narrator. The final Orlando's maturing in the sense of an androgynous creature suggests the utopian idea of joining male and female mind in a unique experience.
Keywords: literary genre; Bildungsroman; parody; biography; androgyny